EmpoWord : a student-centered anthology & handbook for college writers - Abrams, Shane; Portland State University. Library; BC Open Textbook Project; BCcampus (Portland State University Library, 2018)
"EmpoWord is a reader and rhetoric that champions the possibilities of student writing. The textbook uses actual student writing to exemplify effective writing strategies, celebrating dedicated college writing students to encourage and instruct their successors: the students in your class. Through both creative and traditional activities, readers are encouraged to explore a variety of rhetorical situations to become more critical agents of reading, writing, speaking, and listening in all facets of their lives. Straightforward and readable instruction sections introduce key vocabulary, concepts, and strategies. Three culminating assignments (Descriptive Personal Narrative; Text-Wrestling Analysis; Persuasive Research Essay) give students a chance to show their learning while also practicing rhetorical awareness techniques for future writing situations. This textbook is designed for students of first- and second-year college composition courses, but it is also a great tool for college prep students, more advanced writers, or independent learners"--BCcampus website.
Part One: Description, Narration, and Reflection. Chapter One: Describing a Scene or Experience -- Chapter Two: Telling a Story -- Chapter Three: Reflecting on an Experience -- Assignment: Descriptive Personal Narrative -- Part Two: Text Wrestling. Chapter Four: Interpretation, Analysis, and Close Reading -- Chapter Five: Summary and Reader-Response -- Chapter Six: Analysis and Synthesis -- Assignment: Text wrestling Analysis -- Part Three: Research and Argumentation. Chapter Seven: Argumentation -- Chapter Eight: Research Concepts -- Chapter Nine: Interacting with Sources -- Assignment: Persuasive Research Essay.
This work is licensed under the Creative Commons Attribution-NonCommercial CC-BY-NC.
This bibliographic record is available under the Creative Commons CC0 "No Rights Reserved" license.
Includes bibliographical references.
Mode of access: World Wide Web.
Online version, 2018; title from PDF (viewed on September 5, 2018).
Keywords: English language -- Study and teaching (Higher); English language -- Grammar -- Study and teaching (Higher); English language -- Rhetoric -- Study and teaching -- Handbooks, manuals, etc